The demographic role of religion in Hungary: Fertility of denominations at the beginning of the 20th century - Harrach, Gabe (Hungarian Geographical Bulletin, 2013)
Could it be possible that religious ties determine demographic behaviour, including fertility? If so, how can we arrange this factor with other variables in the same causal hierarchy? The raised problems were drafted at the beginning of modern demography already. In this paper we examine the mutual relations of religion, ethnicity and fertility in the territory of the former Hungarian Kingdom at the beginning of the 20th century. This period is interesting for the fact that fertility rate in Hungary decreased by an extraordinary proportion, 40% between 1910 and 1930. The Carpathian Basin had a unique ethnic and religious character at that time: seven main ethnic groups and seven relevant denominations had been registered by the 1910 Hungarian Census, thus the region is suitable for the empirical examinations of the mentioned coherences.